2008
DOI: 10.1063/1.2996277
|View full text |Cite
|
Sign up to set email alerts
|

Programmable manipulation of motile cells in optoelectronic tweezers using a grayscale image

Abstract: This paper describes a grayscale optoelectronic tweezers (OET) which allows adjustment of the electric field strength at each position of OET. A grayscale light image was used to pattern vertical electric field strength on an OET. As an electric field depends on the brightness at each point, the brighter light patterns generate the stronger electric field in the OET. Its feasibility for application to cell manipulation was demonstrated by aligning highly motile protozoan cells in vertical direction. Depending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…[11][12][13][14][15][16] Recent studies of electro-orientation have revealed its ability to orient bacteria and nanowires. [17][18][19] Dielectrophoresis provides for concentration and sorting capabilities 11,12,16 and electro-orientation allows for the alignment of asymmetric particles on a macro scale. 20 Several methods for integration of electrodes with microfluidic channels have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Recent studies of electro-orientation have revealed its ability to orient bacteria and nanowires. [17][18][19] Dielectrophoresis provides for concentration and sorting capabilities 11,12,16 and electro-orientation allows for the alignment of asymmetric particles on a macro scale. 20 Several methods for integration of electrodes with microfluidic channels have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the optically induced torque in OEK chips has been exploited to adjust highly motile protozoan cells' moving direction [97] and induce cell selfrotation [93]. The latter method (i.e., cell self-rotation in an OEK chip) has the potential to be used to identify cell types and elucidate the electrical and physical properties of cells.…”
Section: Biological Entities: Cells and Moleculesmentioning
confidence: 99%
“…Thus, collecting enough data in a limited amount of time requires improvement in the efficiency of observing microorganism motions along a specific direction. Z-directional (perpendicular to the top and bottom surfaces of the microfluidic channel) electromanipulation is expected to improve the efficiency of front-view observation of continuously swimming microorganisms 17,19,32,46 . To this end, electrodes with a square outline (side length of outer square ≈1000 μm, side length of inner square (observation window) ≈500 μm, thus electrode width ≈250 μm), shown in Figure 4a, were prepared on the top and bottom of the interior walls of a microchannel (~1100 μm wide, 500 μm high) using hybrid fs laser microfabrication.…”
Section: Z-directional Electro-orientation Of Microorganisms In Glassmentioning
confidence: 99%
“…The optimum frequencies for the orientation depend on the electrical and geometrical parameters of the cells and the conductivity of the cell suspensions. The electro-orientation of not only many elongated biological samples, such as E. coli (bacteria) 17,18 , B. subtilis (bacteria) 18 , S. marcescens (bacteria) 9 , T. pyriformis (ciliates) 19 , microtubules 20 , cardiac myocytes 21 , retinal photoreceptors 22 , ellipsoidal erythrocytes 23 , and yeast cells 24,25 , but also one-dimensional (1D) nanomaterials, such as nanowires and nanorods [26][27][28] , have been demonstrated. Electro-orientation in microfluidic chips has already been demonstrated for some important applications, such as the optical detection of bacteria 17 , the dielectric measurement of microtubules 20 , and cardiac tissue engineering 21 .…”
Section: Introductionmentioning
confidence: 99%